ANALISIS PERSEPSI ORANG DALAM KEPERCAYAAN MENGGUNAKAN CRYPTOCURRENCY DI INDONESIA - Hendi Sama; Nelson (LPPM Sekolah Tinggi Teknologi Pagar Alam, 2022)
This study aims to determine people's perceptions of trust in using cryptocurrency in Indonesia. This study uses a qualitative and quantitative approach with Cryptocurrency and Blockchain variables as independent variables and Trust as the dependent variable. In the qualitative method, 30 samples of people who used cryptocurrency were taken and in the quantitative method, 400 samples were taken of people who used cryptocurrency with a population as of July 2021 of 7.4 million based on data from the Commodity Futures Trading Supervisory Agency (Bappebti) of the Ministry of Trade (Ministry of Trade). The method of collecting data on the qualitative approach is the interview method while the quantitative approach uses the method of distributing questionnaires. Data analysis uses the SPSS application, for qualitative data it will be codified first. Based on the results of qualitative and quantitative data analysis, the authors conclude that the Cryptocurrency and Blockchain variables partially and simultaneously affect the Trust variable with percentages of 87.8% and 73.2% respectively.